Group Size Effects in Public Goods Provision: The Voluntary Contributions Mechanism - Isaac, R. Mark; Walker, James M. (Quarterly Journal of Economics, 1988)
This paper examines the relationship between variations in group size and “free-riding” behavior in the voluntary provision of public goods. We examine experimentally two pertinent concepts: the marginal return to an individual from contributions to the public good, and the actual number of members in the group. Our results strongly support a hypothesis that increasing group size leads to a reduction in allocative efficiency when accompanied by a decrease in marginal return from the public good (as from crowding or an association of large groups with imperceptibility of marginal benefits). Our results do not support a pure numbers-in-the-group effect.